Peran Kepuasan Kerja dalam Memediasi Pengaruh Pengembangan Karir dan Budaya Organisasi terhadap Retensi Karyawan - Sudarijati, Sudarijati; Ismartaya, Ismartaya; Nurani, Arinta (Jurnal Ilmiah Global Education, 2025)
Career development and a strong organizational culture are believe to enhance job satisfaction, which in turns encourages to remain with the company. This study aims to analyze the influence of career development and organizational culture on employee retention, with job satisfaction as an intervening variable, at PT Graha Karya Informasi. a descriptive quantitative approach was employed, involving 181 respondents, and the data were analyzed using path analysis. The results show that career development and organizational culture have a direct and positive effect on both job satisfaction and employee retention. Job satisfaction also has a direct and positive impact on employee retention, and it indireclty mediates the relationship between career development and organizational culture with employee retention. Based on these findings, it is recommended that the company strengthen career development programs and foster an organizational culture that supports job satisfaction and increases employees’ intention to remain with the organization.